Analysis of Organizational Culture, Organizational Commitment, and Work Behavior on Employee Performance Mediated by Work Ethics - Esti Liana Susanto; Aang Gunawan; Oce Prasetya; Erni Pratiwi Perwitasari; Primadi Candra Susanto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The purpose of this study is to develop hypotheses related to factors that influence employee performance, especially in aviation companies in Indonesia. The approach used in this literature review study is descriptive qualitative. The data collection technique used is a literature study or review of relevant previous articles published between 2021 and 2026. The technique used in this literature review is comparative analysis. The data used in this descriptive qualitative approach came from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this literature review are: 1) Organizational Culture s employee work ethics in aviation companies; 2) Organizational Commitment influences employee work ethics in aviation companies; 3) Work Behavior influences employee work ethics in aviation companies; 4) Organizational Culture influences employee performance in aviation companies; 5) Organizational Commitment influences the Performance of airline company employees; 6) Work Behavior influences the Performance of airline company employees; 7) Work Ethics influence the Performance of airline company employees; 8) Organizational Culture influences Employee Performance through the Work Ethics of airline companies; 9) Organizational Commitment influences Employee Performance through the Work Ethics of airline companies; 10) Work Behavior influences Employee Performance through the Work Ethics of airline companies.